Blocking Interleukin-1β in Acute and Chronic Autoinflammatory Diseases - Dinarello, Charles A. (2011)
An expanding spectrum of acute and chronic inflammatory diseases are considered “autoinflammatory” diseases. This review considers autoinflammatory diseases as being distinct from “autoimmune” diseases. Autoimmune diseases are associated with dysfunctional T-cells and treated with “biologicals” including anti-TNFα, CTLA-Ig, anti-IL-12/23, anti-CD20, anti-IL-17 and anti-IL-6 receptor. In contrast, autoinflammatory diseases are uniquely due to a dysfunctional monocyte caspase-1 activity and secretion of IL-1β; indeed, blocking IL-1β results in a rapid and sustained reduction in the severity of most autoinflammatory diseases. Flares of gout, Type-2 diabetes, heart failure and smoldering multiple myeloma are examples of seemingly unrelated diseases, which are uniquely responsive to IL-1β neutralization.